Cesium activates the neurotransmitter receptor for glycine - Fricke, Steffen; Harnau, Magnus; Hetsch, Florian; Liu, Haoran; Leonhard, Julia; Eylmann, Anna; Knauff, Pina; Sun, Han; Semtner, Marcus; Meier, Jochen C. (Frontiers in Molecular Neuroscience, 2023)
The monovalent cations sodium and potassium are crucial for the proper functioning of excitable cells, but, in addition, other monovalent alkali metal ions such as cesium and lithium can also affect neuronal physiology. For instance, there have been recent reports of adverse effects resulting from self-administered high concentrations of cesium in disease conditions, prompting the Food and Drug Administration (FDA) to issue an alert concerning cesium chloride. As we recently found that the monovalent cation NH4+ activates glycine receptors (GlyRs), we investigated the effects of alkali metal ions on the function of the GlyR, which belongs to one of the most widely distributed neurotransmitter receptors in the peripheral and central nervous systems. Whole-cell voltage clamp electrophysiology was performed with HEK293T cells transiently expressing different splice and RNA-edited variants of GlyR α2 and α3 homopentameric channels. By examining the influence of various milli- and sub-millimolar concentrations of lithium, sodium, potassium, and cesium on these GlyRs in comparison to its natural ligand glycine (0.1 mM), we could show that cesium activates GlyRs in a concentration- and post-transcriptional-dependent way. Additionally, we conducted atomistic molecular dynamic simulations on GlyR α3 embedded in a membrane bilayer with potassium and cesium, respectively. The simulations revealed slightly different GlyR-ion binding profiles for potassium and cesium, identifying interactions near the glycine binding pocket (potassium and cesium) and close to the RNA-edited site (cesium) in the extracellular GlyR domain. Together, these findings show that cesium acts as an agonist of GlyRs.